An Infrared View of the Obscured AGN Environment in NGC 4945 - Gaspar, Gaia (2022)
NGC 4945 harbors one of the nearest active galactic nuclei (AGNs), which allows us to reach high spatial resolution with current observational facilities. The Seyfert 2 nucleus is deeply obscured by an edge-on disk with A V ∼14, requiring infrared observations to study circumnuclear structures and the interstellar medium. In this work, we present an imaging and long-slit spectroscopic study of the nuclear region with a spatial resolution of 6.5 pc, based on Flamingos-2 (F2) and T-ReCS data taken at the Gemini South observatory. We report subarcsecond photometric measurements of the nucleus in J, H, and K s filters, and at larger apertures. We do not detect nuclear variability. The nuclear spectra confirm that even in the K band the AGN emission-line features are completely obscured by dust. We detect a circumnuclear disk in the K band as well as in the mid-infrared N and Q abands, with a radial scale length of ∼120 pc. The disk shows knots mostly in a ring-like arrangement that has been previously detected with Paα observations from the Hubble Space Telescope, indicating that these are deeply embedded, massive young star clusters. We present here the spectrum of one of the brightest unresolved objects (R < 5 pc), which we identify as a super star cluster candidate with MKs-16.6±0.4 . For the circumnuclear region, a detailed rotation curve allows us to measure a nuclear mass of M = (4.4 ± 3) × 106 M ⊙ within a radius of ∼6.5 pc. We also report the detection of hot dust (∼1000 K) out to a nuclear distance of 80 pc measured along the semimajor axis.